Prevalence of simple liver cysts and hemangiomas in cirrhotic and non-cirrhotic patients submitted to magnetic resonance imaging - Galvão,Breno Victor Tomaz (2013)
Objective To determine the prevalence of liver cysts and hemangiomas in the general population and in cirrhotic patients. Materials and Methods Retrospective, observational, and cross-sectional study selecting consecutive magnetic resonance imaging studies performed in the period from February to July 2011. A total of 303 patients (187 women and 116 men) with mean age of 53.3 years were included in the present study. Patients with previously known liver lesions were excluded. The images were consensually analyzed by two observers in the search for simple liver cysts and typical liver hemangiomas, according to universally accepted imaging criteria. Lesions prevalence, diameters and location were determined in both cirrhotic and non-cirrhotic individuals. Results The authors observed prevalence of 8.6% for hemangiomas and 14.5% for simple cysts. No statistically significant difference was observed in relation to prevalence of hemangiomas and cysts among cirrhotic and non-cirrhotic patients (p = 0.954; p = 0.472). Conclusion In the present study, the prevalence of cysts and hemangiomas was higher than the prevalence reported by autopsy series. No influence of cirrhosis was observed on the prevalence and appearance of such incidental lesions.